Homeopathy in Sleep Health: A Journey through Efficacy, Challenges & Research Frontiers (Homoeopathy for All, 2024)
plays a critical role in  maintaining physical and mental  health. It is essential for various  bodily functions such as cognitive  processing, emotional regulation,  and systemic homeostasis.1 The  quality of sleep significantly impacts  overall well-being, with poor sleep  linked to various health issues,  including cardiovascular diseases,  obesity, diabetes, and mental  health disorders like depression  and anxiety.2, 3 In recent years,  the prevalence of sleep disorders  has been rising, with common  conditions including insomnia,  characterized by difficulty in falling  or staying asleep; sleep apnea,  marked by interrupted breathing  during sleep; restless leg syndrome,  featuring an uncontrollable urge to  move the legs; and circadian rhythm  disorders, affecting the sleep-wake  cycle.4 These conditions not only  diminish quality of life but also pose  a burden on healthcare systems.
Keywords: anxiety; uncontrollable; breathing